The impact of technology adoption, prowgrowth absorptive capacity, knowledge sharing, and financial planning on business performance in the Food and Beverage Industri - Aryo Pinandito; Rifqi Muafiyah; Nia Wulandari; Rika Amanda (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
In the Industry 4.0 era, technology adoption has become a crucial determinant of business sustainability and competitiveness in the food and beverage (F&B) sector. This study aims to analyze the effects of technology adoption, pro-growth absorptive capacity, knowledge sharing, and financial planning on business performance among micro, small, and medium enterprises (MSMEs) in West Java, Indonesia. Using a quantitative approach with Structural Equation Modeling (SEM–AMOS 24) and 696 valid responses, each construct was measured using multiple indicators adapted from previous studies with proven reliability and validity. The findings show that technology adoption significantly enhances pro-growth absorptive capacity, which in turn strongly improves business performance. Knowledge sharing and absorptive capacity contribute positively to financial planning, yet financial planning itself has only a marginal effect on business performance. Furthermore, absorptive capacity does not mediate the relationship between technology adoption, knowledge sharing, and financial planning on performance, suggesting the potential influence of other contextual factors such as leadership or organizational culture. Overall, the study highlights that strengthening absorptive capacity and integrating technology adoption are key strategies to boost business performance, while financial planning and knowledge sharing serve as supportive enablers when embedded within a technology-driven learning culture. Future research is recommended to include moderating variables and longitudinal approaches to better capture the dynamics of digital transformation in MSMEs.